Investigating the effect of magnetic field on the slip flow behavior of air-fluid in a rectangular microchannel - Mohsen Saghafian; Mehdi Moslehi; Omid Ali Akbari (International Journal of Thermofluids)
In this research, we numerically model the heat transfer problem in electronic devices using appropriate assumptions and boundary conditions close to reality, which has been mentioned in fewer studies. In this study, the space between the slider and the hard disk is simulated as a two-dimensional microchannel with specific boundary conditions affected by the magnetic field. In a microchannel with asymmetric wall heating, uniform heat flux, and influenced by a uniform magnetic field, the study numerically investigates laminar flow and forced convection heat transfer of a Newtonian fluid. The model assumes a first-order behavior for slip velocity and temperature change at the channel walls. The interplay among Hartmann number (M), Knudsen number (Kn), and heat flux ratio (rq) is visualized using tables and graphs, depicting their effects on velocity and temperature fields. The maximum velocity and velocity gradient at the channel wall both increase as M grows, while the maximum velocity decreases. Magnetic fields have a smaller impact on temperature variations compared to velocity variations. At higher Knudsen values, the magnetic force has a greater impact on velocity and temperature distributions. The Hartmann number's increase causes a slight uptick in the average Nusselt number. Increasing M causes a substantial decrease in the friction factor. The Hartmann number's growth does not significantly affect thermal entrance length.